SAT0049 Obesity is Associated with Reduced Improvement in Functional Disability After 1 Year of Treatment: Results from an Inception Early Rheumatoid Arthritis Cohort. (23rd January 2014) - Ling, S. F.; Chitale, S.; Estrach, C.; Moots, R. J.; Goodson, N.
Abstract : Background: Disease outcomes in rheumatoid arthritis (RA) may be influenced by a patient's body mass index (BMI). Previous work has shown improved radiographic outcomes in obese RA patients 1 . However, obesity is associated with higher disease activity at baseline and reduced rates of DAS28 remission after 1 year of treatment 2 . A recent study in inflammatory polyarthritis found an association between BMI≥35kg/m 2 and increased disability at presentation (measured using health assessment questionnaire, HAQ) 3 . Obesity may impact adversely on other RA disease outcome measures at 1 year. Objectives: To explore whether baseline obesity is associated with improved functional disability after 1 year of disease-modifying (DMARD) therapy. Methods: An inception cohort of eRA patients (i.e. with clinical diagnosis of RA of symptom duration <1 year) were identified from an early arthritis clinic. At initial assessment, symptom duration, DAS28, rheumatoid factor and anti-citrullinated protein antibody (ACPA) statuses and HAQ scores were recorded. BMI was calculated (in kg/m 2 ) and divided into 3 categories: 1) Underweight/normal BMI<25; 2) Overweight BMI 25-29.9; and 3) Obese BMI ≥30. All received DMARDs following a targeted treatment protocol. HAQ improvement at 1 year was calculated and divided into 3 categories: 1) Worsening HAQ score; 2) Minimal HAQ improvement, 0-1; and 3) Good HAQ improvement, >1. Associations between baseline BMI category and 1) HAQ scores at baseline; and 2) Change in HAQ score at 1 year, were explored using logistic regression, adjusting for age, gender and smoking status. Results: 193 eRA patients with 1-year follow-up data were identified. At baseline, mean age was 58.1 (SD 15.0), 62.7% were female and 68.9% were ACPA positive (+). DMARD use was similar across BMIs. Median BMI was 28 [IQR 24.7, 31.7]. 31.1% of patients were obese. Of obese patients, 71.7% were female and mean age was 55.8 (SD11.8). At baseline, median HAQ was 1 [IQR 0.5, 1.5] and no association between BMI and HAQ was seen. At 1 year, 36.7% of obese patients achieved DAS28 remission, versus 52.8% in non-obese patients. Obesity was inversely associated with good improvement in HAQ scores (ORadj 0.4 [95% CI 0.2, 0.9], p=0.036). Subgroup analyses revealed stronger associations in 1) Female patients (ORadj 0.3 [95% CI 0.1, 0.9], p=0.032); and 2) ACPA+ patients (ORadj 0.2 [95% CI 0.1, 0.8], p=0.022). Conclusions: Obese eRA patients are less likely to achieve good HAQ improvement after 1 year of treatment, despite similar DMARD therapy to non-obese patients. This may reflect persistent disease activity associated with obesity as well as obesity-associated functional disability. Obesity appears to be an important confounder and should be adjusted for in studies exploring disability outcomes in response to treatment in eRA patients. Obesity in eRA appears to be a poor prognostic marker for treatment response. References: Van der Helm-van Mil AH et al. Ann Rheum Dis 2008;67:769-74. Ling S et al. Rheumatology 2012;51(Suppl 3):iii162. Humphreys JH et al. Arthrit Care Res 2013;65:122-6. Disclosure of Interest: None Declared